1986
DOI: 10.1093/jac/17.suppl_a.25
|View full text |Cite
|
Sign up to set email alerts
|

The new quinolones and their combinations with other agents for therapy of severe infections

Abstract: New quinolones are very potent compounds against Gram-negative bacteria, including Pseudomonas, and staphylococci. They are particularly interesting because of their oral availability and their pharmacokinetic properties. When combined with other common antibiotics they appear to have mostly indifferent effects in vitro. Clinical results have shown their efficacy when used alone for the treatment of osteomyelitis, complicated urinary tract infections and prostatitis. Nevertheless, in 6% of cases resistant stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Three activities are responsible for this modification: acetylation, nucleotidylation, and phosphorylation. Amikacin is considered by some to be the aminoglycoside of choice for severe nosocomial infections, especially when it is used in combination with P-lactams or fluoroquinolones (9). In gram-negative bacteria, only three enzymes capable of leading to resistance to this drug have been identified: aminoglycoside 6'-N-acetyltransferase type I [AAC(6')-I], 3'-O-phosphotransferase type VI [APH(3')-VI], and 4'-O-nucleotidyltransferase [ANT(4')].…”
mentioning
confidence: 99%
“…Three activities are responsible for this modification: acetylation, nucleotidylation, and phosphorylation. Amikacin is considered by some to be the aminoglycoside of choice for severe nosocomial infections, especially when it is used in combination with P-lactams or fluoroquinolones (9). In gram-negative bacteria, only three enzymes capable of leading to resistance to this drug have been identified: aminoglycoside 6'-N-acetyltransferase type I [AAC(6')-I], 3'-O-phosphotransferase type VI [APH(3')-VI], and 4'-O-nucleotidyltransferase [ANT(4')].…”
mentioning
confidence: 99%
“…The current study demonstrated that the MICs of the quinolones for 34 strains of P. pseudomallei were lower than commonly achievable concentrations in serum of the five agents tested (2,4). Ciprofloxacin was the most effective agent, with an MIC for 90% of the strains tested of 8 ,ug/ml.…”
mentioning
confidence: 57%
“…No strains were noted to be susceptible to the other four antimicrobial agents. On the basis of achievable levels in blood (2,4) and our susceptibility data, the fluoroquinolones would not be considered appropriate …”
mentioning
confidence: 99%
“…In an open study, Ramirez [27] treated and cured three cases of arthritis due to N. gonorrhoeae and S. pneumoniae with ciprofloxacin. Remarkable results were obtained by Desplaces et al [28] with a combination of pefloxacin (400 mg twice daily) plus rifampin in patients with chronic osteomyelitis due to S. aureus. Fourteen of 14 patients were cured, with a follow-up of Waldvogel 9-24 months, results that confirm the experimental data described previously.…”
Section: Clinical Studiesmentioning
confidence: 90%